The cnidarian origin of the proto-oncogenes NF-κB/STAT and WNT-like oncogenic pathway drives the ctenophores (Review) - SINKOVICS, JOSEPH G. (Int J Oncol, 2015)
The cell survival pathways of the diploblastic early multicellular eukaryotic hosts contain and operate the molecular machinery resembling those of malignantly transformed individual cells of highly advanced multicellular hosts (including Homo). In the present review, the STAT/NF-κB pathway of the cnidarian Nematostella vectensis is compared with that of human tumors (malignant lymphomas, including Reed-Sternberg cells) pointing out similarities, including possible viral initiation in both cases. In the ctenophore genome and proteome, β-catenin gains intranuclear advantages due to a physiologically weak destructive complex in the cytoplasm, and lack of natural inhibitors (the Dickkopfs). Thus, a scenario similar to what tumor cells initiate and achieve is presented through several constitutive loss-of-function type mutations in the destructive complex and in the elimination of inhibitors. Vice versa, malignantly transformed individual cells of advanced multicellular hosts assume pheno-genotypic resemblance to cells of unicellular or early multicellular hosts, and presumably to their ancient predecessors, by returning to the semblance of immortality and to the resumption of the state of high degree of resistance to physicochemical insults. Human leukemogenic and oncogenic pathways are presented for comparisons. The supreme bioengineers RNA/DNA complex encoded both the malignantly transformed immortal cell and the human cerebral cortex. The former generates molecules for the immortality of cellular life in the Universe. The latter invents the inhibitors of the process in order to gain control over it.